Age-related and Individual Variation in Male Piezodorus hybneri (Heteroptera: Pentatomidae) Pheromones - Nobuyuki Endo; Tetsuya Yasuda; Takashi Wada; Shin-etsu Muto; Rikiya Sasaki (Psyche: A Journal of Entomology)
Males of the Piezodorus hybneri stink bug produce a pheromone comprising β-sesquiphellandrene (Sesq), (R)-15-hexadecanolide (R15), and methyl (Z)-8-hexadecenoate (Z8). We collected airborne volatiles from individual P. hybneri males and analyzed them by GC-MS. Daily analysis from 1 to 16 days after adult emergence showed that pheromone emission started around 3 to 6 days after adult emergence and peaked (~1 μg/male/day) on day 11. The proportion of Sesq tended to increase with age to about 80% on days 12 to 16. On the other hand, the proportion of R15 tended to decrease with age. The proportion of Z8 reached a maximum of about 34% on day 9 but otherwise remained below 20%. The total amount of pheromone emitted by individual males varied considerably: three males emitted more than 10 μg, whereas another three males emitted little or no pheromone and failed to survive by the end of the experiment. These results suggest that the amount of P. hybneri pheromone and its blend ratio could be affected by the male’s physical conditions, such as vitality and age.